Vacancies Engineering in Molybdenum Boride MBene Nanosheets to Activate Room-Temperature Ferromagnetism - Zhang, Liangzhu (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.